Potensi Tepung Ampas Tebu sebagai Bahan Pembuatan Bagasse Biscuits untuk Terapi Konstipasi - Firjatu, Putri Chalya; Sitompul, Dea Syafira Alamsyah; Siregar, Zahra Arridhani; Azzahra, Shafa Rizki (Talenta Publisher, 2022)
Background: Bagasse is a by-product of the sugarcane process. In Indonesia, bagasse is rarely used as a raw material for making food. Sugarcane bagasse is high in fiber. On the other hand, high rate of constipation in Indonesia requires a high-fiber food product solution. Objectives: This study aims to determine whether bagasse flour can be used as an ingredient for Bagasse Biscuits, to find out the level of people's preferences, the nutritional content of Bagasse Biscuits, and its correlation to constipation. Methods: This study consisted of three treatments, P1, P2, and P3 respectively at 100%, 50%, and 20% of bagasse flour. The research started by collecting recipes of biscuit literature. The literature is used as a reference to get the right recipe. Before the biscuits are made, the bagasse flour tested in laboratory to determine its nutritional content. Then, the biscuit organoleptic test was carried out to 50 respondents by distributing questionnaires containing assessments of taste, texture, color, and aroma. Furthermore, laboratory tests were conducted on biscuits with the highest organoleptic test values. Results: Bagasse flour contains 30.62% carbohydrates, 1.71% protein, 49.51% fiber, and 0.29% fat. Based on the organoleptic test, it was found that respondents preferred Bagasse Biscuits P3 with a taste aspect of 3.96 (delicious), texture 3.12 (soft), color 3.94 (beige chocolate), and aroma 3.96 (strong biscuit aroma). The nutritional content test was carried out on Bagasse Biscuits P3, carbohydrates 11.82%, protein 8.9%, fiber 32.39%, and fat 25.73%. Conclusion: bagasse waste which is processed into flour can be used as an ingredient for making Bagasse Biscuits because it contains carbohydrates, protein, fiber, and fat. The fiber content is possible to overcome constipation. Keywords : Sugarcane Bagasse, Biscuits, Constipation